ESTRATÉGIAS DE RESISTÊNCIA DO MOVIMENTO CAMPONÊS BRASILEIRO EM FRENTE DAS NOVAS TÁTICAS DE CONTROLE DO AGRONEGÓCIO TRANSNACIONAL - Welch, Clifford Andrew (REVISTA NERA, 2012)
The article surveys strategies developed by Brazilian rural social movements to combat the hegemony of transnational agricultural corporations and agribusinesses utilizing biotechnologies such as transgenic seed to gain control of agricultural production and commodity markets.